Phosphate removal from real wastewater using maghemite beads - Simonič, Marjana (Array, 2019)
The present study aimed at research of phosphate adsorption onto poly(vinyl-alcohol) PVA alginate beads in comparison with maghemite modified beads from wastewater. The characterisation of material was performed by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction. The influence of pH and the quantity of maghemite nanoparticle was studied. The results of phosphate adsorption onto PVA-alginate beads showed 45 % of initial PO43- concentration removal from wastewater while the maghemite PVA-alginate beads showed better adsorption activity at 70 % of initial PO43- removal. The optimal dose was determined at 0.9 g of PVA-M beads (containing 0.01 g maghemite) added to the 50 mL wastewater. The efficiency of phosphate removal from wastewater was relatively low due to content of coexistent anions, including SO42−, CO32−, NO3− and Cl−, which compete with phosphate for the binding sites, hindering PO43− to form inner sphere complexes.